Understanding Compensation Practice Variations Across Firms: The Impact of National Culture - Schuler, Randall S.; Rogovsky, Nikolai (Journal of International Business Studies, 1998)
With operations spread worldwide, firms that find themselves competing in a global marketplace are looking at the implications of the admonition, “When in Rome.…” This raises the question: “Do cultures of countries have an impact on the generally accepted methods of managing human resources?” The answer to this question is the focus of this article. By developing culture-specific propositions for four categories of compensation practices based on status, performance, social benefits and programs, and employee ownership plans, we seek to determine the extent to which Hofstede's four dimensions of culture are associated with specific compensation practices. Support is found for most of the propositions. The implications of the finding for the management of human resources by multinational firms are discussed.